Early Development of Locomotor Patterns and Motor Control in Very Young Children at High Risk of Cerebral Palsy, a Longitudinal Case Series - Bekius, Annike; Bach, Margit M.; van de Pol, Laura A.; Harlaar, Jaap; Daffertshofer, Andreas; Dominici, Nadia; Buizer, Annemieke I. (Frontiers in Human Neuroscience, 2021)
The first years of life might be critical for encouraging independent walking in children with cerebral palsy (CP). We sought to identify mechanisms that may underlie the impaired development of walking in three young children with early brain lesions, at high risk of CP, via comprehensive instrumented longitudinal assessments of locomotor patterns and muscle activation during walking. We followed three children (P1-P3) with early brain lesions, at high risk of CP, during five consecutive gait analysis sessions covering a period of one to two years, starting before the onset of independent walking, and including the session during the first independent steps. In the course of the study, P1 did not develop CP, P2 was diagnosed with unilateral and P3 with bilateral CP. We monitored the early development of locomotor patterns over time via general gait parameters, intersegmental coordination (estimated via principal component analysis), electromyography activity, and muscle synergies (determined from eleven bilateral muscles via non-negative matrix factorization). P1 and P2 started to walk independently at the corrected age of 14 and 22 months, respectively. In both of them, general gait parameters, intersegmental coordination, muscle activation patterns and muscle synergy structure changed from supported to independent walking, although to a lesser extent when unilateral CP was diagnosed (P2), especially for the most affected leg. The child with bilateral CP (P3) did not develop independent walking and all the parameters did not change over time. Our exploratory longitudinal study revealed differences in maturation of locomotor patterns between children with divergent developmental trajectories. We succeeded in identifying mechanisms that may underlie impaired walking development in very young children at high risk of CP. When verified in larger sample sizes, our approach may be considered a means to improve prognosis and to pinpoint possible targets for early intervention.